Point-of-Care Ultrasound for Monitoring Congestion and Guiding Decongestion Therapy in Heart Failure: A Narrative Review - Bernad, Mateusz; Widomska, Katarzyna; Bender, Aleksandra; Walczak, Paulina; Niewęgłowska, Małgorzata; Szymulewicz, Bartłomiej; Dąbrowski, Kacper; Łukaszewicz, Jakub; Krazińska, Oliwia; Gałach, Magdalena; Figiel, Aniela; Zaborek, Paweł; et al. (Quality in Sport, 2026)
Background: Heart failure (HF) remains one of the leading causes of hospitalization worldwide. Accurate assessment of congestion is crucial for optimal management, yet traditional diagnostic approaches such as physical examination, chest radiography, and natriuretic peptide measurements have limited sensitivity for detecting early or subclinical congestion. Point-of-care ultrasonography (POCUS) has emerged as a promising bedside tool that allows rapid and repeatable assessment of pulmonary and systemic congestion. Aim: This review aims to summarize the current evidence regarding the use of point-of-care ultrasonography in monitoring congestion and guiding decongestion therapy in patients with heart failure. Material and methods: A structured literature search was conducted across three major databases: PubMed, SciSpace (Basic and Full Text), and Google Scholar. The search strategy employed Boolean operators combining Medical Subject Headings (MeSH) and relevant keywords related to heart failure, point-of-care ultrasound, lung ultrasound, and decongestion therapy. Retrieved publications were screened for relevance and duplicates were removed. Results: The initial search identified 685 records. After deduplication and relevance assessment, 211 unique publications were identified and compiled into a structured database. The 30 most relevant studies formed the primary evidence base for this narrative review. The available evidence suggests that POCUS particularly lung ultrasound and inferior vena cava assessment may improve detection of congestion and support optimization of decongestion therapy in HF patients. Conclusions: Current evidence indicates that integration of POCUS into HF management may enhance monitoring of congestion and potentially improve therapeutic decision-making. However, further prospective studies and standardized clinical protocols are required to confirm its impact on clinical outcomes.